The encoding of word forms into memory may be challenging for college students with developmental language impairment. (2nd January 2017) - McGregor, Karla; Arbisi-Kelm, Tim; Eden, Nichole
Abstract: Purpose : To describe the word-learning problems characteristic of developmental language impairment (LI). Method : College students with LI ( n = 39) or normal language development (ND, n = 40) attempted to learn novel word forms. Training for half of the words was meaning-focused; training for the other half was form-focused. Form recognition and stem completion tasks administered immediately after training tapped encoding of the lexical configuration and a repetition of the stem completion task one week later tapped consolidation. A visual world paradigm tapped lexical engagement. Result : At the immediate post-test, the LI group was poorer at recognition and completion of word forms than their ND peers, suggesting a deficit in encoding the lexical configuration. However, the gap between the LI and ND groups in stem completion did not grow over the week, suggesting intact consolidation. Form-focused training yielded better performance than meaning-focused training at immediate- and one week tests. For both groups, newly trained words slowed the recognition of familiar English words, revealing lexical engagement. Conclusion : The encoding of word-form configurations is challenging for some, but not all, college students with LI. Training that encourages a focus on the form may be a useful part of vocabulary intervention for those affected.